Keberkesanan Pengajaran Kursus Titas 1: Kajian di Universiti Teknologi Mara, Shah Alam - Haji Othman, Mohamad Khairi (Jurnal Usuluddin, 2004)
This article based on the findings of the study done by the writer to investigate the students perception of the effectiveness of the Islamic and Asia Civilization Course 1 (TITAS 1) at MARA University of Technology. The aspects of the effectiveness looked into are related to its objectives, lecture modules, its rationale and student interest. Data collection was done through the questionnaire. The results show that the TITAS 1 course met its objectives, lectures are practical and of high quality, the course is beneficial and important, and students are interested with this course.